The Water We Drink : Water Quality and Its Effects on Health - Barzilay, Joshua I., 1951- (Book collections on Project MUSE., 1999)
Briefly traces the history of sanitation and disease, discusses links between water and infectious diseases, cancer, and infertility, and looks at bottled water and water purification.